The Innovation Policy of the Świętokrzyskie Voivodeship - Kraska, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This article discuses an important issue about stimulate innovation on the example of the świętokrzyskie voivodeship. At the beginning author presented the level of innovation in the świętokrzyskie region. Next she made attempts to explained of this situation. The last section describes how local government implemented the aims included in regional innovation strategy.